PENGEMBANGAN PERANGKAT PEMBELAJARAN STATISTIKA MELALUI PENDEKATAN REALISTIK DENGAN KONTEKS COVID-19 PADA SISWA SMA - Uci Mahlisa; Nursiah (Jurnal Binagogik, 2025)
Teachers' efforts to develop mathematics learning tools must not only be aligned with the curriculum but also with the context of real-world problems occurring in the students' environments. Numerous studies have been conducted on the use of context in mathematics learning. However, learning tools that utilize the COVID-19 context are still limited. The main objective of this research is to develop statistics learning tools through a realistic approach within the COVID-19 context that are valid, practical, and effective. To achieve this goal, development research was conducted using the Tessmer model, which consists of preliminary phases, self-evaluation, expert review, one-to-one, small group, and field testing. The results show that the developed learning tools meet the criteria for validity, practicality, and effectiveness. Validity is achieved because all validators have stated that the developed learning tools are theoretically and empirically valid. The development of the tools is based on a strong theoretical foundation and the components are interconnected and consistent. The developed learning tools meet the practical criteria because the validators stated that the developed learning tools can be theoretically implemented in the field, and the results of the learning implementation test meet the criteria for very good. The effectiveness of the learning device was achieved because the trial results showed that the learning device met five of the six established effectiveness indicators: an average percentage of results on assigned tasks of 91%, an average student activity of 90%, a match between observed student activities and expected student activities of more than 80%, a positive student response to the developed learning device of more than 50%, and a positive teacher response to the developed learning device.